OFDM Towards Broadband Wireless Access. - Jha, Uma Shanker (Artech House Universal Personal Communications., 2007)
Presenting the state-of-the-art in broadband wireless access technology, this unique resource shows you how to design OFDM transceivers and develop a novel wireless transceiver system architecture one that streamlines wireless system development and deployment because of its reusability, scalability and flexibility. The book gives you a solid understanding of reconfigurable baseband transceiver architecture, fixed broadband access, and 802.16 (WiMax) and 802.20 network design.